Exploring the impact of dimensional comparisons in health contexts. Issue 7 (12th May 2022) - Edmonds, Keith A.; Rose, Jason P.
Abstract: "Did I exercise enough this week?" "Should I eat that last donut?" "Am I in good shape?" Due to the ambiguity and difficulty of answering such questions, people often use comparison‐based information to contextualize their standing, inform self‐evaluations, and guide behavior. For example, to ascertain whether they have exercised enough, people can make social comparisons to peers (e.g., "Have I exercised more than my friends?") or temporal comparisons of the present to the past (e.g., "Have I exercised more this week than last week?"). While ample research has examined the relevance and impact of social and temporal comparisons in a range of health contexts (e.g., health behaviors, risk perceptions), the overarching goal of the present review was to explicate the potential relevance and impact of a third type of comparison standard— dimensional comparisons —in health contexts (with an emphasis on health behaviors like exercise). First, we discuss how social and temporal comparisons shape self‐evaluations in both health and non‐health contexts. Second, we provide an overview of research conducted on dimensional comparisons in non‐health contexts and discuss how comparison sources shape self‐evaluations and self‐concept formation. Third, we explore the potential impact and relevance of dimensional comparisons on self‐evaluations in health behavior contexts. Fourth, and finally, we highlight potential future directions and considerations for advancing our knowledge of the relevance and influence of dimensional comparisons in health contexts.